Formulation Optimization of Extemporaneous Oral Liquids Containing Naloxone and Propranolol for Pediatric Use - Maria Attebäck; Bengt Hedin; Sofia Mattsson (MDPI AG, 2022)
There is a need to develop dosage forms suitable for children to improve drug treatment. Extemporaneous compounding of drugs for children is one way to meet these needs. However, excipients generally considered as safe in adults may not be appropriate in dosage forms intended for children. The aim was to optimize the composition of two pediatric liquid preparations by substituting paraben as a microbiological preservative and ethanol as a solubilizer, with excipients more suitable for pediatric use. The oral liquids were Naloxone 1 mg/mL and Propranolol 10 mg/mL. Twelve different formulations were tested with propranolol and naloxone, respectively, during the screening process to select appropriate formulations. Sodium benzoate and glycerol were used as a preservative and solubilizer, respectively, and different pH of the formulations were evaluated. The formulations were characterized according to dispensed dose (dosing accuracy), viscosity and osmolality. The optimized formulations from the screening process were tested with two amounts of sodium benzoate and microbiological assays were performed. These formulations were shown to have satisfactory preservative properties and dosing accuracy. The results showed that the oral liquids could be prepared without the addition of solubilizer and with lower osmolality (naloxone), thus reducing the risk of gastrointestinal side effects.